Body of State - Baliani, Marco,Marini-Maio, Nicoletta,Nerenberg, Ellen,Simpson, Thomas (Fairleigh Dickinson University Press, 2011)
Body of State offers a critical perspective on the Moro Affair and on Marco Baliani's work. With contributions from scholars, theater practitioners, teachers, and students, it constitutes a unique resource for disciplines that train on the intersection of art and politics. The relevance of the topic raise the interest of the audience as well.
Description based on publisher supplied metadata and other sources
Keywords: Moro; Aldo; Mord; Innenpolitik